2016
DOI: 10.1038/nature17665
|View full text |Cite
|
Sign up to set email alerts
|

Musashi-2 attenuates AHR signalling to expand human haematopoietic stem cells

Abstract: Umbilical cord blood (CB)-derived hematopoietic stem cells (HSCs) are essential in many life saving regenerative therapies, but their low number in CB units has significantly restricted their clinical use despite the advantages they provide during transplantation1. Select small molecules that enhance hematopoietic stem and progenitor cell (HSPC) expansion in culture have been identified2,3, however, in many cases their mechanisms of action or the nature of the pathways they impinge on are poorly understood. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
121
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(130 citation statements)
references
References 38 publications
(53 reference statements)
9
121
0
Order By: Relevance
“…The above-mentioned conclusion is consistent with our earlier findings where expression of some AhR-dependent genes was compared between both, differentiated and undifferentiated, unmodified HepaRG cells [41]. The conclusion is consistent also with the findings of involvement of AhR in development of fetal mouse liver [42] or control of expansion of human hematopoietic stem cells in culture [66]. It was demonstrated that different cell types were involved in AhR-dependent development of mouse liver and in AhR-dependent hepatotoxicity [43].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The above-mentioned conclusion is consistent with our earlier findings where expression of some AhR-dependent genes was compared between both, differentiated and undifferentiated, unmodified HepaRG cells [41]. The conclusion is consistent also with the findings of involvement of AhR in development of fetal mouse liver [42] or control of expansion of human hematopoietic stem cells in culture [66]. It was demonstrated that different cell types were involved in AhR-dependent development of mouse liver and in AhR-dependent hepatotoxicity [43].…”
Section: Discussionsupporting
confidence: 91%
“…Participation of the aryl hydrocarbon receptor in induction of expression of genes connected to regulation of apoptosis or involved in cell proliferation from one side, and in inhibition of genes connected to cell adhesion from the other side could explain some results suggesting involvement of AhR not only in initiation but also in progression of cancer [83]. In agreement with above, novel physiological function for AhR has been proposed recently, as regulator of self-renewal of hematopoietic stem cells [66] or in general, modulator of the balance between differentiation and pluripotentiality in normal and transformed tumor cells [84]. …”
Section: Discussionmentioning
confidence: 81%
“…MSI2 overexpression in a conditional murine system results in a transient increase in HSC numbers, and retroviral overexpression results in improved engraftment 16 . Consistent with its role in mouse HSCs, forced expression of MSI2 in human cord blood cells resulted in a 23-fold ex vivo expansion of long-term repopulating activity and a 17-fold increase in short-term repopulating activity 18 . Loss of Msi2 expression in a murine germline gene trap mutant has opposing effects; LSK (Lineage Low , Sca1 + , c-Kit + stem and progenitor) cells are reduced resulting in poor engraftment and a defect in lymphoid primed multipotent progenitor cell (LMPP) activity due to decreased cycling 17 .…”
Section: Msi Family and Hematopoietic Stem And Progenitor Cellsmentioning
confidence: 63%
“…Msi2 is better known for its role in regulating translation, and our analysis now adds another possible mechanism by which it may influence HSCs. Interestingly, overexpression of human MSI2 was reported to expand HSCs via attenuation of the aryl hydrocarbon receptor pathway as an RNA-binding protein (Rentas et al., 2016). MSI2 also plays a role in malignancy, thus understanding the possible relevance of splicing and RNA regulation in normal stem cells may reveal another layer of regulation (and mis-regulation) in cancer and in cancer stem cells (Barbouti et al., 2003, de Andres-Aguayo et al., 2011, Kharas et al., 2010).…”
Section: Discussionmentioning
confidence: 99%